Determinan Kinerja Keuangan Pada Umkm Di Wilayah Pontianak Kota - Kharisma, Tasya (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to determine the effect of financial literacy (X1) and financial management (X2) on financial performance. The sample was taken from 60 respondents using purposive and convience samples. The analysis techniques used are data instrument testing, classical assumption testing, multiple linear regression, and hypothesis testing. The data collection method is by distributing questionnaires to MSMEs in the food and beverage sector in the Pontianak City area. The research results show that variable financial literacy (X1) and financial management (X2) have a positive and significant effect on the financial performance (Y) of MSMEs in the Pontianak City area.